Quantitative Microbial Risk Assessment for Escherichia coli in Drinking Water in Bandarharjo Village, Semarang, Indonesia - Putri, Vidia Nabilah; Sulistiyani, Sulistiyani; Raharjo, Mursid (International Journal of English Literature and Social Sciences (IJELS), 2020)
Universal access to safe drinking water is a basic need and a human right. Drinking water contamination can occur in the household. One of the bacteria that can contaminate water is Escherichia coli which can cause gastrointestinal disease. The purpose of this study was to conduct a microbial risk assessment of drinking water contaminated with Escherichia coli bacteria in the Bandarharjo Village. This research is a descriptive study with the Quantitative Microbial Risk Assessment (QMRA) method. The sample in this study consisted of 94 people as subjects and 94 samples of drinking water as object samples. The sampling technique used is proportional random sampling. The results showed that as many as 51drinking water samples (54,3%) did not meet the requirements. The average intake and frequency of exposure are 1,63 liters and 365 days/year. The results of the QMRA calculation show that the average value of the probability of infection per day and the probability of infection per year are 2,12 x 10-5 and 7,7 x 10-3. The research concludes that the probability of infection per year is greater than the acceptable risk by US EPA, which is 10-4.